Systematic errors in annotations of truncations, loss-of-function and synonymous variants - Vihinen, Mauno (Frontiers in Genetics, 2023)
Description of genetic phenomena and variations requires exact language and concepts. Vast amounts of variation data are produced with next generation sequencing pipelines. The obtained variations are automatically annotated e.g. for their functional consequences. These tools and pipelines, along with systematic nomenclature, mainly work well, but there are still some problems in nomenclature, organization of some databases, misuse of concepts and certain practices. Therefore, systematic errors prevent correct annotation and often preclude further analysis of certain variation types. Problems and solutions are described for presumed protein truncations, variants that are claimed to be of loss-of-function based on the type of variation, and synonymous variants that are not synonymous and lead to amino acid changes or to missing protein.